2020
DOI: 10.3390/ma13173857
|View full text |Cite
|
Sign up to set email alerts
|

A Polyethylene Base Moisture Activating Oxygen Scavenging Film Co-Extruded with Tea Polyphenols-β-Cyclodextrin Inclusion Complex

Abstract: Antioxidant packaging is an effective method to protect oxygen-sensitive food from oxidation. In order to concurrently obtain a storage stability and excellent oxygen scavenging of antioxidant film for the high moisture food, a moisture activating oxygen scavenging film was prepared by using tea polyphenols as the oxygen scavenger. The moisture activating function was achieved by introducing the β-cyclodextrin embedding technology, and the tea polyphenols–β-cyclodextrin inclusion complex was co-extruded with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Despite the high price, α-tocopherol is used to stabilize polyethylene medical devices [ 11 , 12 , 13 ]. Moreover, compounds of natural origin that have been proposed in the scientific literature as stabilizers for polymer materials include carotenoids, polyphenolic compounds (flavonoids, curcuminoids, phenolic acids) and phenolic polymers (lignin, tannin) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high price, α-tocopherol is used to stabilize polyethylene medical devices [ 11 , 12 , 13 ]. Moreover, compounds of natural origin that have been proposed in the scientific literature as stabilizers for polymer materials include carotenoids, polyphenolic compounds (flavonoids, curcuminoids, phenolic acids) and phenolic polymers (lignin, tannin) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Assynthesized Bt in ethanol solution (5 mM) was further used for conjugation with BCD (5 mM) in DI H 2 O using a 1:1 molar ratio. The conjugate was prepared by adding the ethanolic solution of Bt in a dropwise manner into the aqueous BCD solution while stirring at 500 rpm, 80 °C for 4 h. Then, the mixture was lyophilized at −80 °C for 48 h. 27 After lyophilization, the residual solvents in the conjugated materials were removed by evaporation at 60 °C for 2 h to obtain the BCD-Bt bioconjugates. The final conjugated sample of BCD-Bt appeared to be a pale yellow-colored powder.…”
Section: Conjugation Of Bcd With Btmentioning
confidence: 99%
“…Figure 3b showed that the scavenging activity of the 3-layer active film was slightly slower and lower at lower temperature (7 • C), and higher deviation values between samples were found. The increase in oxygen scavenging activity with the temperature has also been observed when using antioxidants as oxygen scavenger, such as gallic acid and tea polyphenols, because their activities increased at higher temperatures [28,29].…”
Section: Oxygen Scavenging Of Tor-containing Filmsmentioning
confidence: 99%